Implementasi Program Kampus Mengajar Dalam Meningkatkan Mutu Pendidikan di SDN 45 Gresik - Fika Khoirotul Jannah; Ardhana Januar Mahardhan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of implementing the Teaching Campus program is to create collaboration between students and teachers in the field to assist the teaching process in elementary schools. The Teaching Campus Program is one form of activity from the implementation of the Merdeka Learning Campus Merdeka (MBKM) from the Ministry of Education and Culture of the Republic of Indonesia. The focus in this paper is to look at the implementation of the Teaching Campus program as an effort to improve the quality of education. The research method used is a qualitative approach. The research location is at SDN 45 Gresik, East Java with the research subjects being students, teachers, and principals at the school. Data was collected by using observation, interview, and documentation techniques. From the research results, it is known that the implementation of the Teaching Campus program is very helpful in carrying out the tasks at SDN 45 Gresik, this can be seen from the collaborative activities carried out between students and teachers, including: (1) helping the learning process, (2) helping technology adaptation, and (3) assisting school administration.